Ownership, Wealth, and Risk Taking: Evidence on Private Equity Fund Managers - Carsten Bienz; Karin Thorburn; Uwe Walz (Leibniz Institute for Financial Research SAFE, 2019)
We examine the incentive effects of private equity (PE) professionals' ownership in the funds they manage. In a simple model, we show that managers select less risky firms and use more debt financing the higher their ownership. We test these predictions for a sample of PE funds in Norway, where the professionals' private wealth is public. Consistent with the model, firm risk decreases and leverage increases with the manager's ownership in the fund, but largely only when scaled with her wealth. Moreover, the higher the ownership, the smaller is each individual investment, increasing fund diversification. Our results suggest that wealth is of first-order importance when designing incentive contracts requiring PE fund managers to coinvest.
Keywords: D86; G12; G31; G32; G34; 330; Private equity; buyouts; incentives; general partner; ownership; risk taking; wealth